The Australian Annuity Market - Knox, David M. (World Bank, Washington, DC, 2014)
In Australia, a means-tested old-age public pension is paid from general tax revenues. A full pension (equivalent to roughly a quarter of the average wage) is currently paid to more than half the aged population, and a reduced pension is paid to another quarter of the aged population. About 20 percent receive no old-age public pension because of the level of their income or assets. There is also a compulsory system under which employers contribute at least 7 percent of salaries into a superannuation plan for the vast majority of employees. (This minimum rate will gradually rise to 9 percent in 2002.) More than 80 percent of superannuation benefits are received as lump sums; when public sector employees are excluded, the figure rises to almost 90 percent. The market for private life annuities with longevity insurance is very small. Greater use is made of allocated annuities, which are similar to income drawdowns in the United Kingdom or scheduled withdrawals in Latin American countries. The value of life annuities, measured by the money's worth ratio, compares favorably with that of annuities available in the United Kingdom and United States. But these ratios are calculated on the basis of conservative government bond yields. Many investors prefer allocated annuities--which are perceived to offer considerable advantages in flexibility and higher potential returns--despite the absence of longevity insurance.